What moves you? shaping your dissertation in dance - Nichol, Charlotte; Uytterhoeven, Lise (London New York, NY Routledge, 2017)
Every dissertation is individual and unique - particularly for dance students, who must combine a wide range of approaches into tailor-made research methodology. What Moves You? fosters a creative approach to dissertations and final projects. By guiding the development of a personal study program, this volume encourages dance students to take ownership of their artistic and academic work, a skill essential both to successful undergraduate study, and to making the first steps towards a career in dance. Rather than propose a prescriptive, step-by-step mantra, Charlotte Nichol and Lise Uytterhoeven draw upon contributions from students, teachers, examiners and practitioners to broaden the notion of 'research' and demystify the purpose of the dissertation
Designing your research project -- Anchor points in your learning process -- Thinking on your feet : the research process -- Outward facing : presenting and communicating the research -- Beyond the dissertation, into working life.
Includes bibliographical references
Keywords: Dissertations, Academic -- Handbooks, manuals, etc; Dance -- Research -- Methodology -- Handbooks, manuals, etc